Nutritional quality of maca stubble (Lepidium peruvianum Chacón) in guinea pigs - Castro Bedriñana, Jorge (2018)
The objective of this study was to evaluate the nutritional quality of maca stubbles (Lepidium peruvianum Chacon) from threshing for the collection of botanical seed, in the province of Junín (4000 m above the sea level), Peru. The proximal chemical composition and the digestibility coefficients, the total digestible nutrient contents, the voluntary consumption, and the protein intake of the maca stubbles were determined. Four 4- month-old male Wanka guinea pigs were placed in metabolic cages to collect urine-free faeces. The contents of moisture (H), dry matter (DM), total protein (TP), ether extract (EE), crude fibre (CF), nitrogen-free extract (NFE) and ash of maca stubbles were 11.30, 88.70, 6.97, 3.58, 36.35, 44.53 and 8.58%, respectively; the digestibility coefficients of the DM, PT, EE, EC, ELN, organic matter (OM) and total digestible nutrients of maca stubbles were 74.79, 68.00, 75.27, 71.78, 77.08, 74.21 and 71.21%, respectively. The average consumptions of fresh maca stubbles per guinea pig/day and as a percentage of live weight were 21.46 g and 3.25%, respectively; while the consumption of DM as a percentage of live weight and in grams per kilogram of metabolic weight was 2.89% and 146.11 g, respectively. The average daily protein intake per kilogram of live guinea pig was 2 g.